Pengaruh Model Cooperative Learning Terhadap Peningkatan Pemahaman Konsep Matematika Dan Keaktifan Belajar - Yustiara, Dana; Kusumastuti, Mimin Nurjhani; Ramdhani, Sendi (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
The aim of this study is to examine the effect of a cooperative learning model on improving the understanding of mathematical concepts and fostering greater engagement in learning among fourth-grade students at SDN Gebang Raya 2, Tangerang Regency. The type of research used was quasi-experimental design. The study's population consists of 83 students with sample size of 56 students. The data analysis for this study involved the utilization of both the t-test and MANOVA test, facilitated by the SPSS 23.0 software for Windows. The hypothesis testing conducted in this study to assess the effect of the cooperative learning model on learning engagement yielded a p-value, or significance value, of 0.000 (p < 0.005). Additionally, when evaluating the influence of the cooperative learning model on both the comprehension of mathematical concepts and learning engagement, the resulting p-value was also 0.000 (p < 0.005). The conclusion of this study is that there is an effect of the cooperative learning model towards the student's understanding of mathematical concepts and their engagement in learning in Gebang Raya 2 Elementary School.